Evaluation of Single- versus Dual-Tube Thoracostomy after Thoracotomy for Trauma. Issue 10 (October 2017) - Hardin, Jeremy; Strumwasser, Aaron; Grabo, Daniel; Kleinman, John; Inaba, Kenji; Demetriades, Demetrios
Draining the chest cavity with two chest tubes after thoracotomy for trauma is controversial. This article aims to determine whether using two tubes after thoracotomy for trauma is more effective than using a single tube. A 9-year retrospective review (2007–2015) was performed at our academic level I trauma center. All patients who underwent trauma thoracotomy (unilateral and bilateral) were included for analysis (n = 99). Patients with incomplete data, pediatric patients (age < 18), pregnant patients, and early deaths (<24 hours) were excluded. When analyzed by chest cavity, dual tubes have increased drainage bilaterally (P = 0.008) and require more days to clear the right chest (P = 0.002). Patients with dual tubes bilaterally are associated with increased intensive care unit length of stay (P = 0.05) and ventilator days (P = 0.04). Although dual chest tube insertion achieves greater drainage, it comes at the cost of increased time to clear the chest and is associated with worse outcomes in bilateral injuries. One chest tube may be sufficient post-trauma thoracotomy; routine placement of two chest tubes is not recommended.